Perbandingan Arbitrase Hubungan Industrial Dengan Pengadilan Hubungan Industrial - Rusli, Hardijan (Pelita Harapan University, 2005)
Conflicting interests, disagreement on rights, dispute over work termination of working contract and/or dispute between workers union within one corporation may easily and frequently arise in labour or industrial relation due to lack ofcovergence of opinions in the drowning up of, and/or changes of the working conditions or company regulation or in the collective labour agreement. One of the dispute resolution over interests and workers unions recognized by law is the so- called Extra-judicial Settlement Procedure, beside that of within the court system namely Industrial Relation Court. This extra-judicial settlement procedure, which may be termed as Industrial Relation Arbitration, is a written agreement between parties in dispute recognizing and invoking a settlement procedure upon which those parties agreed that the judgment made by this arbiter is binding and final. The parties also agree that such final judgment may not be submitted to the Industrial Relation Court for further examination. This writing is dealing with the comparison of those two settlement procedures convening to resolve the worker and/or labour related legal problems in pursuant to the Law No. 2 of 2004 on the Industrial Relation Court.